2020
DOI: 10.3389/fnins.2020.00645
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability as an Index of Differential Brain Dynamics at Rest and After Acute Stress Induction

Abstract: The brain continuously receives input from the internal and external environment. Using this information, the brain exerts its influence on both itself and the body to facilitate an appropriate response. The dynamic interplay between the brain and the heart and how external conditions modulate this relationship deserves attention. In high-stress situations, synchrony between various brain regions such as the prefrontal cortex and the heart may alter. This flexibility is believed to facilitate transitions betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 92 publications
1
50
0
Order By: Relevance
“…Recently, some studies have shown evidence of the association between PFC regions and HRV parameters. Chand et al (2020) observed an association between HRV and brain networks including cortical regions such as the ventromedial PFC. Prefrontal cortex activity is also related to changes in HRV parameters via the mediation of the cortico-subcortical pathways that modulate the parasympathetic and sympathetic nervous systems (Nikolin et al, 2017).…”
mentioning
confidence: 95%
“…Recently, some studies have shown evidence of the association between PFC regions and HRV parameters. Chand et al (2020) observed an association between HRV and brain networks including cortical regions such as the ventromedial PFC. Prefrontal cortex activity is also related to changes in HRV parameters via the mediation of the cortico-subcortical pathways that modulate the parasympathetic and sympathetic nervous systems (Nikolin et al, 2017).…”
mentioning
confidence: 95%
“…Importantly, Benarroch highlighted the role of specific CAN regions such as the insula, anterior hypothalamus, nucleus of tractus solitarius, or ventral medulla in the genesis of cardiac arrhythmias and sudden death in neurological diseases, suggesting the central role of CAN in the cardiac rhythm control. With functional neuroimaging, it has been possible to delineate in vivo the anatomical correlates of brain activity for HRV changes induced by cognitive, emotional, or physical tasks 22 , or at rest 23 25 . In a model proposed by Thayer 16 , the right mPFC, in an interconnected network with the cingulate cortex and the insula, exerts through GABAergic projections to the central nucleus of the amygdala (CeA) a tonic inhibitory control of subcortical sympathetic cardioacceleratory outputs that the hypothalamus, periaqueductal gray matter, and the parabrachial pontine nuclei have on the rostral ventrolateral medulla, and allows the activation of parasympathetic cardioinhibitory neurons of the medulla in the nucleus ambiguus and the dorsal motor nucleus of vagus.…”
Section: Discussionmentioning
confidence: 99%
“…The observations in humans and experimental studies in animals have helped to identify the central autonomic network (CAN), which encompasses the main integrative control centers of the ANS 17 19 . The use of non-invasive brain-imaging methods, such as functional MRI (fMRI), has also helped to characterize CAN in healthy subjects 20 , and its modulatory role for autonomic parameters such as HRV 21 25 . In PD, neuropathological evidence supports the involvement of structures belonging to CAN 26 , while the degree of sympathetic myocardial denervation does not fully explain the observed heart rate abnormalities 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Whilst our study augments prior findings which have heavily relied on associations between HRV and functional connectivity during rest by assessing heart-brain function in an active emotion regulatory context, the current study and the majority of prior work have typically relied on relatively static functional connectivity techniques. Although a few studies have examined transient HRV changes and functional connectivity using dynamic functional connectivity (dFC) techniques such as the sliding window approach (Chand et al, 2020; Chang et al, 2013; Schumann et al, 2021a), this method is limited by its reliance on arbitrary selection of truncated time windows to assess both functional connectivity and HRV, with the latter particularly affected by the shorter duration of the measurement period (Shaffer & Ginsberg, 2017; TaskForce, 1996). It would therefore be fruitful for future research to employ novel and alternative dFC methods that overcome existing constraints (e.g., co-activation pattern analysis; Liu et al, 2013, 2018) to determine associations between HRV and dynamic neural networks underlying adaptive and flexible regulation across the lifespan.…”
Section: Discussionmentioning
confidence: 99%